Gestational diabetes mellitus: study of prevalence using criteria of diabetes in pregnancy study group in India and its impact on maternal and fetal outcome in a rural tertiary institute - Swaroop, Neelam; Rawat, Rajani; Lal, Pavika; Pal, Naresh; Kumari, Kalpana; Sharma, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gestational diabetes mellitus ((GDM) is defined as carbohydrate intolerance of varying degree of severity with onset or first recognition during pregnancy. GDM is associated with adverse fetomaternal outcome. Its early detection and management is essential for better perinatal outcome. The objective of the study was to assess the prevalence of gestational diabetes mellitus among pregnant women of western U.P. using diabetes in pregnancy study group in India (DIPSI) criteria and further assess its impact on fetomaternal outcome. Methods: This was a prospective study conducted at UP RIMS & R, Saifai, Uttar Pradesh, India including 225 pregnant women between 24-28 weeks gestational age who attended the antenatal OPD from January 2014 to January 2015.All women were given 75 gm oral glucose irrespective of their meals. Women with blood sugar values >140mg/dl were labeled as GDM and rest as control or non GDM group. All the GDM patients were followed up either with diet or insulin therapy till delivery to study fetomaternal outcome. Results: Out of 225 Women 22 women (9.7%) were diagnosed as having GDM and among risk factors, higher BMI was shown to be significant association (p<0.05). There was also significant difference among birth weight and neonatal complications in GDM and NON-GDM group (P<0.05). Conclusions: Due to high prevalence of GDM in India in our study we concluded that screening is very essential for all pregnant women even in low-risk group. As in our study which was done by single step method of DIPSI which was easy to performed, feasible for remote population. But more studies are needed to further conclude that DIPSI is sufficient for Indian population.